Why should we integrate income and employment support? A conceptual and empirical investigation - Antonia Asenjo; Verónica Escudero; Hannah Liepmann (International Labour Organization (ILO), 2022)
The integration of active labour market policies within income support schemes - such as unemployment insurance and social assistance - has been a key component of social protection in high-income countries since the 1990s, with a rich literature reviewing its effects and implementation characteristics. More recently, this approach has spread beyond high-income economies, and is prominent today in many middle-income economies. Yet, despite the increasing adoption of integrated approaches, their conceptual and practical applications have not been studied in detail outside of high-income countries. This paper conceptualizes, for the first time, the implementation of integrated approaches, focusing on low- and middle-income countries (LMIC). We first develop a conceptual framework to understand how integrated policies can address labour market challenges, exploring the theoretical effects they exert on selected labour market and social dimensions. We then contrast these theoretical expectations with findings from the empirical literature on the effectiveness of integrated approaches. While many empirical studies find positive effects across different labour market dimensions, this is evidently not always the case. To reconcile this discrepancy, we investigate the design and implementation of integrated approaches across LMIC and identify factors which contribute to their effectiveness.
Keywords: 330; decent work; employment; informal employment; employment policy; employment creation; employment services; unemployment; conditions of employment; remuneration; low wages; social assistance; unemployment benefits; training; skills; lifelong learning; inequality; poverty; working poor; enterprise creation; household income; informal economy